ANALYSIS OF THE CURRENT STATE OF MARKETING MANAGEMENT OF AGRICULTURAL ENTERPRISES IN UKRAINE - KOVAL, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the current state of marketing management of agricultural enterprises in Ukraine, analyzes key challenges and problems that arise in the process of its implementation. The main factors that affect the effectiveness of marketing activities of agricultural enterprises are identified, in particular, the introduction of digital technologies, adaptation to changes in consumer behavior, diversification of sales channels and the need for a strategic approach to marketing.Considerable attention is paid to problems that hinder the development of marketing management, including insufficient use of digital tools, orientation on traditional sales methods and limited strategic planning. A number of practical recommendations are proposed for improving marketing management, including the integration of innovative technologies, the development of branding, the optimization of communication strategies, the expansion of market opportunities through e-commerce and staff training. It is emphasized that among the economic factors that affect the marketing activities of agricultural enterprises in Ukraine, it is worth emphasizing the fluctuations in the exchange rate, which affects the export and import of agricultural products. It is indicated that the level of inflation has a special impact, which causes an increase in the cost of raw materials, fertilizers, fuel, as well as the investment climate and the availability of credit.The study showed that agricultural enterprises should not only focus on traditional markets, but also more actively implement online platforms, marketplaces, expand cooperation with retail chains and establish direct sales of products to the end consumer. Investment in the development of marketing skills of personnel will contribute to the implementation of modern management approaches and will allow for a prompt response to changes in the market environment.
Keywords: marketing; agricultural enterprises; management; consumers; competitiveness; technologies